Evaluating the Effect of Mudharabah and Murabahah Financing on Return on Assets Mediated by Non-Performing Financing at BMT Hasanah Ponorogo - Febriana, Indri; Ulya, Husna Ni’matul (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: This study explores how mudharabah and murabahah financing affect Return on Asset (ROA) and the role of Non-Performing Financing (NPF) as an intervening variable at BMT Hasanah Ponorogo. Research Methods: This study employs regression analysis with NPF as an intervening variable. The data analyzed are the quarterly financial reports of BMT Hasanah Ponorogo from 2019 to 2023, focusing on the relationships between mudharabah financing, murabahah financing, ROA, and NPF. Results: The analysis reveals that mudharabah and murabahah financing significantly impact ROA directly and through NPF as an intervening variable. An increase in financing can enhance ROA, with NPF mediating the relationship between financing and ROA. Conclusion: This study finds that mudharabah and murabahah financing affect ROA, with NPF as an intervening variable. Effective risk management in financing is crucial for improving ROA at BMT Hasanah Ponorogo.